Multidisciplinary Approach to a Recovery Plan of Historical Buildings - Luciana Orlando (International Journal of Geophysics)
The paper emphasizes the advantages of employing multiple data techniques—geology, GPS, surveys of cracking, boreholes, seismic refraction and electrical resistivity tomography—to image the shallow stratigraphy and hypothesize the cause of instability of an urban area. The study is focused on the joint interpretation of the crack pattern, topographic monitoring and the features of the underground, to define the area affected by instability and the direction of ground motion with the objective to advance a hypothesis on the cause of the instability of the area and to depict the main features. Borehole stratigraphies for a univocal interpretation of the lithology of electrical and seismic data and electrical resistivity tomography to constrain the interpretation of the lateral velocity variations and thickness of seismic bedrock were used. The geophysical surveys reveals to be complementary in the depicting of underground features. The study is approached at small and medium scale.